Translation, reliability, and validity of Japanese version of the Respiratory Distress Observation Scale. - Hideaki Sakuramoto; Chie Hatozaki; Takeshi Unoki; Gen Aikawa; Shunsuke Kobayashi; Saiko Okamoto; Shinichi Shimomura; Ayako Kawasaki; Miwako Fukui (PLoS ONE, 2021)
Dyspnea is a common, distressing symptom of cardiopulmonary and neuromuscular diseases and is defined as "a subjective experience of breathing discomfort that consists of qualitatively distinct sensations that vary in intensity." However, Japanese intensive care units (ICUs) do not routinely screen for dyspnea, as no validated Japanese version of the Respiratory Distress Observation Scale (RDOS) is available. Therefore, we aimed to translate the English version of this questionnaire into Japanese and assess its validity and reliability. To translate the RDOS, we conducted a prospective observational study in a 12-bed ICU of a universal hospital that included 42 healthcare professionals, 10 expert panels, and 128 ventilated patients. The English version was translated into Japanese, and several cross-sectional web-based questionnaires were administered to the healthcare professionals. After completing the translation process, a validity and reliability evaluation was performed in the ventilated patients. Inter-rater reliability was evaluated using Cohen's weighted kappa coefficient. Criterion validity was ascertained based on the correlation between RDOS and the dyspnea visual analog scale. The area under the receiver operating characteristic curve analysis was used to evaluate the ability of the RDOS to identify patients with self-reported dyspnea. The average content validity index at the scale level was 0.95. Data from the 128 patients were collected and analyzed. Cohen's weighted kappa coefficient and the correlation coefficient between the two scales were 0.76 and 0.443 (95% confidence intervals 0.70-0.82 and 0.23-0.62), respectively. For predicting self-reported dyspnea, the area under the receiver operating characteristic curve was 0.81 (95% confidence interval 0.67-0.97). The optimal cutoff used was 1, with a sensitivity and specificity of 0.89 and 0.61, respectively. Our findings indicated that the Japanese version of the RDOS is acceptable for face validity, understandability, criterion validity, and inter-rater reliability in lightly sedated mechanically ventilated patients, indicating its clinical utility.